Sample Student Projects - Fitri Trisnawati; Nabila Naswa Rahmadani; Raudhatul Noer Apriyanti; Mutiah Nabawiya; Mada Aditia Wardhana (Shofanah Media Berkah, 2026)
This article presents a systematic literature review on the effectiveness and implementation challenges of student project models, specifically Project-Based Learning (PBL) and authentic assessment, in preparing graduates for the workforce. This research aims to address two research questions: (1) how the literature describes the effectiveness of these models in developing 21st-century skills and students professional identity; and (2) what systemic challenges exist in their implementation across various disciplines. The study was conducted through the stages of planning, article search and selection, thematic data extraction, narrative synthesis, and report preparation. The findings show that PBL and authentic assessment are highly effective in aligning learning with real-world professional challenges. These models significantly facilitate the development of critical skills such as communication, collaboration, critical thinking, and adaptability, while strengthening the formation of professional identity and student work-readiness. However, implementation faces various multidimensional systemic challenges. These include high time management burdens, gaps in educator competence, limited financial and physical resources, tensions in curriculum design, and group dynamics such as free-rider syndrome and low psychological safety. In conclusion, while effective, the optimization of student project models requires a holistic approach that includes continuous support for educators, adequate resource allocation, alignment of curriculum policies, and strengthening mentoring mechanisms to overcome these barriers.